Incidence and Risk Factors for Acute Kidney Injury Following Mannitol Infusion in Patients With Acute Stroke: A Retrospective Cohort Study. Issue 47 (November 2015) - Lin, Shin-Yi; Tang, Sung-Chun; Tsai, Li-Kai; Yeh, Shin-Joe; Shen, Li-Jiuan; Wu, Fe-Lin Lin; Jeng, Jiann-Shing
Abstract : Abstract: Mannitol, an osmotic diuretic, is commonly used to treat patients with acute brain edema, but its use also increases the risk of developing acute kidney injury (AKI). In this study, we investigated the incidence and risk factors of mannitol-related AKI in acute stroke patients. A total of 432 patients (ischemic stroke 62.3%) >20 years of age who were admitted to the neurocritical care center in a tertiary hospital and received mannitol treatment were enrolled in this study. Clinical parameters including the scores of National Institutes of Health Stroke Scale (NIHSS) at admission, vascular risk factors, laboratory data, and concurrent nephrotoxic medications were registered. Acute kidney injury was defined as an absolute elevation in the serum creatinine (Scr) level of ≥0.3 mg/dL from the baseline or a ≥50% increase in Scr. The incidence of mannitol-related AKI was 6.5% (95% confidence interval, 4.5%–9.3%) in acute stroke patients, 6.3% in patients with ischemic stroke, and 6.7% in patients with intracerebral hemorrhage. Multivariate analysis revealed that diabetes, lower estimated glomerular filtration rate at baseline, higher initial NIHSS score, and concurrent use of diuretics increased the risk of mannitol-related AKI. When present, the combination of these elements displayed an area under the receiver operating characteristic curve of 0.839 (95% confidence interval, 0.770–0.909). In conclusion, mannitol-related AKI is not uncommon in the treatment of acute stroke patients, especially in those with vulnerable risk factors.